Children and the gender earnings gap: Evidence for Australia - Elif Bahar; Natasha Bradshaw; Nathan Deutscher; Maxine Montaigne (The Australian Government, The Treasury, 2023)
This paper uses an event study approach to estimate the impact of children on the gender earnings gap in Australia. We use the Household, Income and Labour Dynamics in Australia (HILDA) survey to show the arrival of children has a large and persistent impact on the gender earnings gap, reducing female earnings by 55 per cent, on average, in the 5 years following parenthood. We further show, using personal income tax data collected by the Australian Tax Office (ATO), that this gap improves only slightly but remains high in the 10 years following the arrival of children. We attribute the gap in earnings to lower participation rates and reduced working hours amongst mothers. Although the decline in earnings for women is very similar regardless of their breadwinner status in the household pre-children, women with greater access to workplace flexibility are more likely to remain employed after having children.
Keywords: J13; J16; J22; J31; 330; children; gender earnings gap; labour supply; wage differential; norms; discrimination; workplace policies